Australocorinae, a new subfamily of Geocoridae (Hemiptera: Heteroptera: Lygaeoidea) from Australia, with descriptions of a new genus and two new species - Malipatil, M. B. (Zootaxa, 2012)
Australocorinae subfam. nov., a new subfamily of family Geocoridae, is erected for Australocoris gen. nov. containing three species, A. kurandae Kirkaldy, 1908, A. fuscomaculatus sp. nov., and A. monticolus sp. nov., all from Queensland, Australia. Australocoris monticolus has been collected only from northern Queensland, near Julatten north of Cairns to Bellenden Ker Range area, and mostly at higher altitudes 800  to 1560 m; A. kurandae from usually lower altitudes of northern Queensland; and A. fuscomaculatus is known from southern Queensland. The affinities of the subfamily are discussed in relation to other subfamilies of Geocoridae as well as other related families of Lygaeoidea. Geocoridae is redefined to contain this new subfamily. A key to species is provided.